GENERAL CHARACTERISTICS OF THE SUPERCLASS MYRIAPODA - DEEPAK KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
In spite of the fact that naturalists first started paying attention to Myriapoda in 1874, the contributions made by naturalists to our knowledge of the various places on the group are weak and deficient. Since that time, very little progress has been accomplished, which may be at least partially attributable to the fact that the group as a whole does not have any economic significance, the members of the group live extremely long lives, and their reatrioted occurrenue.Those of New Port (1&1) and Fabre are credited with having done the early studies on the male reproductive system of millipedes (1855). Fabre discussed a single species from each of the families Julidae, Glorneridae, Polyxenidae, and Polydesmidae, whereas New Port restricted his investigation to the family Julidae. The only aspect of the gonopods' exterior anatomy that was included in Fabre's description was that part. Von Rath added further details to the material that was already available on the masculine rnpmduti8 qatem of polvdeamur - u-a* mb othor gods (1890). A+tr)mr (1894) provided a more in-depth description of the aal gonopod of a variety of millipedes; nevertheless, he did not go into sufficient detail about the internal anatomy of these structures. This was carried out not too much later on.